A History of Reshaping Australian Telecommunications: A Review of John Doyle’s Crossed Lines: Disruption, Politics and Reshaping Australian Telecommunications - Brett, Judith (Journal of Telecommunications and the Digital Economy, 2022)
A review of John Doyle’s, Crossed Lines: Disruption, Politics and Reshaping Australian Telecommunications, published by Australian Scholarly Publishing, 2022.